An experimental study on the performance of air conditioning system using R-134a And MC-134 refrigerant in D8R caterpillar units - Chalermpol Plengsa-ard; Gunawan Gunawan; Puji Saksono; Jainal Abidin (Journal of Engineering and Applied Technology, 2022)
Refrigerant is a crucial cooling component for the refrigeration cycle. In heavy equipment, the cooling system still relies on the R-134a unit with many weaknesses, including global warming effects and other air conditioning system problems. An alternative substitute for R-134a has been found, i.e., a hydrocarbon refrigerant or MC-134. This product has several advantages compared to R-134a, especially its environmentally friendly aspect. It does not contribute to the damage of the ozone layer and is completed with good physical characteristics and thermodynamic properties. Overall, it has better performance than R-134a, proven on the Nissan Evalia unit. This study aimed at testing heavy equipment, especially the D8R caterpillar unit because limited studies discuss heavy equipment regarding its MC-134performance. This research was carried out at the Petrosea Ltd workshop. The research was done through experimental methods. The first stage was retrofitting R-134a with MC-134 on the D8R caterpillar unit. The data collection was conducted ten times with an interval of 3 minutes. The second step WAS using MC-134 and taking the same data as the first step. The compressor work on the MC-134 increased by 145.96% compared to R-134a. The result of the study showed that the heat energy released by the condenser using MC-134 increased by 157.833%. 161.625% for the refrigeration effect, and 5.21% of The COP value, respectively, compared to R-134a.